2020
DOI: 10.1007/978-3-030-47240-5_16
|View full text |Cite
|
Sign up to set email alerts
|

InnoMetrics Dashboard: The Design, and Implementation of the Adaptable Dashboard for Energy-Efficient Applications Using Open Source Tools

Abstract: Increasing amount of data the organizations worldwide have at their disposal lead to the need to structure, organize and present the information obtained from it. That is because, in today's rapid-changing business environment, managers and executives need to be able to gain crucial insights about the ongoing project in as little time as possible. Recently, energy efficiency has become a greater field of research, and companies started concentrating on monitoring energy-related metrics. In addition, many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…What elements can be adapted within a smart city dashboard? Based on the research questions and considering other terms obtained from previous research [16][17][18]9], we identified the following key words that are consistent with what is proposed to be found: "Smart city", "Adaptable dashboard", "Information visuali*ation", and "Key performance indicator". Once the terms had been defined, they were used to create the search string (S1): S1.…”
Section: Research Processmentioning
confidence: 73%
See 2 more Smart Citations
“…What elements can be adapted within a smart city dashboard? Based on the research questions and considering other terms obtained from previous research [16][17][18]9], we identified the following key words that are consistent with what is proposed to be found: "Smart city", "Adaptable dashboard", "Information visuali*ation", and "Key performance indicator". Once the terms had been defined, they were used to create the search string (S1): S1.…”
Section: Research Processmentioning
confidence: 73%
“…Decision-makers can contrast the data through visual components (either static or real-time KPIs) to make comparisons and inferences to improve city operations [21] [22]. One of the biggest challenges of dashboards for smart cities is to satisfy the different information visualization needs of users to ensure that they are useful in their decision making [9]. In the current development of dashboards for smart cities, the aim is to provide the user with visual representations of data that are part of several screens [23].…”
Section: Qualitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of micro-services can be characterized as the ease of maintainability, scalability, and cross-functional team maintenance. In order to provide a prototype that will help us to start the data collection process and validate our data model, a system with a monolithic API has been developed that contains all the required functionalities such as handling the requests of the data collection components and providing the information needed in the dashboard [16] to be used for data analysis.…”
Section: High-level Architecture Of the Systemmentioning
confidence: 99%
“…First, interactive visualization can aid in model development by providing a functionality for modelers to explore their data and models in ways which are unconventional [6,29]. Such interactions and data exploration allow for the discovery of model features and behaviors which would be difficult to assess using traditional quantitative methods alone and might lead to model refinements, e.g., refined spatial resolution, inclusion/exclusion of assumptions, or adjustments in model parameters or input data [4,7,11]. And second, visual representations of uncertainty which are interactive, in some sense help bring data to life and provide for a more engaging way to convey scientific findings than traditional methods, e.g., bar charts, static maps, or histograms [16,38].…”
Section: Introductionmentioning
confidence: 99%